Predicting lung maturity in preterm rupture of membranes via lamellar bodies count from a vaginal pool: a cohort study - Nachum Zohar; Zafran Noah; Salim Raed; Garmi Gali; Shalev Eliezer (BMC, 2009)
Abstract Background Amniocentesis is the accepted mode of attaining amniotic fluid to perform tests for fetal lung maturity. The purpose of this study was to validate a non-invasive fetal lung maturity test by counting lamellar bodies from a vaginal pool among women with preterm premature rupture of membranes. Methods In a prospective study, amniotic fluid specimens were collected from a vaginal pool from women after preterm premature rupture of membranes with gestational age between 27 and 36 completed weeks. Receiver operating characteristics curve was estimated to assess the threshold of lamellar bodies' count that may predict fetal lung maturity. Results Seventy-five specimens were collected of which 17 were between 32 to 34 weeks. A lamellar bodies' count of 28,000 or more predicted mature fetus 100% of the time (specificity) among all women and also among women between 32 to 34 weeks. The sensitivity was 72% among all and 92% when gestational age was between 32 to 34 weeks. A count of 8,000 or less, predicted respiratory distress syndrome with a sensitivity of 98% among the whole group. Conclusion Counting of lamellar bodies in amniotic fluid from a vaginal pool may be used to predict fetal lung maturity.